PEMBUATAN DODOL PAKEN (DURIO ZIBETHINUS SP.) KHAS KALIMANTAN PADA IBU PKK KELURAHAN MENTENG UNTUK MENDUKUNG EKONOMI KREATIF KOTA PALANGKA RAYA - Indah Gumilang Dwinanda; Kadek Ayu Cintya Adelia; Ety Kurniati; Kharisma Nugraha Putra; Subhan Ilham Thareq (LPPM Universitas Bina Bangsa, 2024)
During the current development period, economic value plays an increasingly important role and the existence of souvenir products is very promising as a business opportunity, plus there are tourism areas, especially in Palangka Raya. Therefore, this training and mentoring activity is encouraged and it is hoped that it can be used by PKK women as a very promising side activity. The more widespread the development of knowledge and skills in food product processing, the tighter the competition in the field of food product processing. Apart from processing, good food packaging that can attract buyers, this is something that needs to be improved. Papaken/Paken (Durio zibethinus sp.) A specific type of fruit that is widely found in Central Kalimantan and is a type of plant that has priority for development in the Multipurpose Tree Type (JPSG) development program. Paken is a plant that grows in almost all areas of Kalimantan. From the results achieved in the activity, the PKK team and women succeeded in making dodol made from paken from Palangka Raya, so it is hoped that in the future it can be produced as a typical Kalimantan souvenir